Penggunaan Metode Field Trip Mangrove Cagar Alam Pulau Dua Terhadap Penguasaan Konsep Siswa - Ratnasari, Dwi; Koosbandiah2, RR Hertien; Supriatno, Bambang (Jurnal Pendidikan Progresif, 2017)
Use of Field Trip Method of Mangrove Pulau Dua Nature Reserve on Mastery of Student Concept. This study aimed to analyze the field trip method Mangrove Pulau Dua Nature Reserve on mastery of student concepts. The research used quasi experiment method with The Matching Only Posttest Only Control Group Design. This research used experimental class and control class with research subject of X grade student in SMA Negeri A of Serang-Banten City. Data obtained from mastery of concepts and questionnaire responses of students regarding the implementation of learning. The results showed that the use of field trip method of Mangrove Pulau Dua Nature Reserve on mastery of students concept is higher than control class. Keywords: Mangrove Pulau Dua Nature Reserve, Field Trip, Mastery of ConceptDOI: http://dx.doi.org/10.23960/jpp.v7.i1.201701